2019
DOI: 10.31703/gssr.2019(iv-ii).46
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Supervisors and Supervisees about Supervisor Role and Responsibilities in Student Research Work

Abstract: The present study seeks to discover the supervisor and supervisees perceptions about supervisor responsibilities in student research work throughout the research process. A selfdeveloped 16 items questionnaire based on the process of thesis work was used to collect data from a sample of 75 supervisors and 200 supervisees who were selected through convenient sampling technique from a university in a metropolitan area of Pakistan. Findings of the study revealed that supervisors held supervisees more responsible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The fourth and the last hypothesis was about moderating the role of supervisor support between cognitive loading and knowledge hiding. This was also accepted as supervisors and their support is necessary in obtaining desired results (Shahzad et al, 2019). Supervisor support is necessary in learning in every medium and is reported by many (Jensen and Solheim, 2020;Swanzy, 2020;Yaghi and Bates, 2020;Gasa and Gumbo, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fourth and the last hypothesis was about moderating the role of supervisor support between cognitive loading and knowledge hiding. This was also accepted as supervisors and their support is necessary in obtaining desired results (Shahzad et al, 2019). Supervisor support is necessary in learning in every medium and is reported by many (Jensen and Solheim, 2020;Swanzy, 2020;Yaghi and Bates, 2020;Gasa and Gumbo, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A supervisor is a person who oversees controlling and regulating students' work in the first level of command. Supervisors keep track of how well pupils complete assignments (Stephens, 2014;Shahzad et al, 2019). Supervisors have an impact on promoting, disciplining, rewarding, altering, and other student-related actions (Swanzy, 2020;Yaghi and Bates, 2020).…”
Section: Moderating Relationship Of Supervisor Supportmentioning
confidence: 99%
“…This finding is congruent with a study conducted in 2015, which indicated that students predominantly expect their supervisors to mentor and guide them in acquiring the necessary research information and skills and then evaluate their work and provide constructive feedback [ 30 ]. Moreover, qualitative research published in 2019, with the aim of examining the role of supervisors’ responsibilities in research projects, revealed that research supervisors are expected to provide emotional and academic support and emphasized the importance of empowering students throughout their research [ 31 ]. Therefore, these findings highlight the importance of conducting an initial supervisor-student meeting to clarify the roles and responsibilities, thereby facilitating the successful completion of the UPRCs.…”
Section: Discussionmentioning
confidence: 99%